BS EN IEC 60794-1-212. Optical fibre cables. Part 1-212. Generic specification. Basic optical cable test procedures. Environmental test methods. Temperature cycling with cable elements fixed at both ends, Method F12 (3rd December 2021) - British Standards Institution,
No abstract available